SELF-REGULATION OF RESTRICTIVE EATING BEHAVIOUR IN INDIVIDUALS UNDER CONDITIONS OF PSYCHOGENIC STRESS - Yatsyuk, Mariia; Pototska, Iryna (Personality and environmental issues, 2026)
Objective. The article aims to provide theoretical substantiation and empirical research on the psychological characteristics of eating behavior under psychogenic stress caused by war events. Methodology. The study employed a comprehensive set of methods: testing (EAT-26, Integrative Anxiety Test, Emotional Dysregulation Questionnaire, A. Ellis Irrational Beliefs Questionnaire), content analysis of self-observation diaries, and statistical processing of data. The sample consisted of 80 individuals aged 18 to 60 years (both males and females) who voluntarily participated in the study observing the principles of psychological ethics. Scientific novelty. For the first time, the construct of «war-related food anxiety» has been identified and described as an integral predictor of maladaptive eating behavior. It is established that under conditions of chronic war stress, a cognitive-restrictive profile of disorders dominates with an overvaluation of weight control, where dietary restrictions (45 % of respondents) prevail over bulimic manifestations. The study reveals that the basis of eating disorders is not specific irrational beliefs about food but fundamental deficits in emotional regulation: avoidance (r=0,557 with general risk index), rumination (r=0,48 with pathological influence), and difficulties in mentalization (r=0,466 with weight control). The correlation analysis confirmed that emotional regulation disorders have significantly closer links with all aspects of eating pathology than classical irrational attitudes, indicating that under chronic traumatic stress, disturbances at the affect level are primary. A negative correlation between age and eating disorders was found (r=-0,3 for weight control), demonstrating higher vulnerability of younger respondents to war stressors in the eating sphere. The study also confirmed the transgenerational transmission of eating patterns through the maternal influence (15 % of respondents with high level), which actualizes in conditions of existential threat. Conclusions. More than half of the respondents (57,5%) are in the zone of increased risk of eating disorders, significantly exceeding the indicators of non-clinical populations in peacetime (10-20 %). War-related food anxiety (high level in 20 % of the sample) reflects an existential fear of deficit and activates archaic mechanisms of «food panic», closely correlating with compulsive overeating (r=0,656), dietary restrictions (r=0,623), and general risk level (r=0,652). Chronic war stress forms a stable anxiety-phobic personality radical with a pronounced asthenic component and a tendency to social isolation. The compensatory eating pattern acts as a maladaptive way of coping with the inability to recognize one's own emotions and mentalize internal states. The high-risk group for compulsive and emotional overeating comprises 23,75 % of the sample, which correlates with international studies on the impact of military conflicts on eating behavior exacerbation. The obtained results emphasize the need for differentiated psychological support programs focused on restoring the basic sense of security, developing mentalization skills, reducing avoidant behavior, and working with rumination, as well as stabilizing asthenic conditions and restoring social connections as an alternative source of support. Prospects for further research include longitudinal studies of the identified disorders' dynamics, in-depth analysis of gender differences, and investigation of resilience factors preventing the formation of maladaptive eating strategies under chronic traumatic stress.